2001
DOI: 10.1016/s0166-4328(01)00283-2
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural testing of standard inbred and 5HT1B knockout mice: implications of absent corpus callosum

Abstract: Rapid advances in biotechnology have created new demands for tests of mouse behaviour having both high reliability and high throughput for mass screening. This paper discusses several statistical and psychological factors pertinent to replication of results in different laboratories, and it considers the question of which inbred strains are best for test standardization. In this context, the problem of absent corpus callosum in the 129 strains is addressed with data from a recent study of six diverse tests of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 36 publications
2
19
1
Order By: Relevance
“…For example, strain PL/J had an average brain weight of 0.506 g in the present study and 0.516 g in the Roderick study but 0.433 g in the Williams data (www.mbl.org), whereas the three studies found similar brain weights for C57BL/6J (0.495 g here, 0.489 for Roderick, and 0.482 for Williams). Previous data on brain size of eight strains from our laboratories [24] are very similar to the present data for the four strains included in both studies, whereas the former study with three laboratories found a significant main effect of laboratory but no significant interaction between strain and laboratory.…”
Section: Discussionsupporting
confidence: 88%
“…For example, strain PL/J had an average brain weight of 0.506 g in the present study and 0.516 g in the Roderick study but 0.433 g in the Williams data (www.mbl.org), whereas the three studies found similar brain weights for C57BL/6J (0.495 g here, 0.489 for Roderick, and 0.482 for Williams). Previous data on brain size of eight strains from our laboratories [24] are very similar to the present data for the four strains included in both studies, whereas the former study with three laboratories found a significant main effect of laboratory but no significant interaction between strain and laboratory.…”
Section: Discussionsupporting
confidence: 88%
“…Only one BALB/cWah1 mouse showed an abnormally small HC, whereas the HC was severely deficient in every 9XCA/Wah animal, including two in which there were almost no HC axons crossing the midline. There was a wide range of size of the CC in BALB/cWah1 mice, but this extreme size variation within BALB/cWah1 was not significantly related to fear conditioning (data not shown), which is consistent with the literature on behavioral sparing in CC agenesis (Schmidt et al, 1991;Bulman-Fleming et al, 1992;Wahlsten et al, 2001). As such, the focus of our analysis was on the difference between strains that arose from grossly different sizes of the HC.…”
Section: Commissural Anatomysupporting
confidence: 87%
“…This developmental variability within a genetically homogeneous strain provides a well controlled experiment of nature to assess the behavioral effects of an absent CC. Surprisingly, hereditary absence of the CC has little or no impact on a wide range of mouse behaviors (Schmidt et al, 1991;Bulman-Fleming et al, 1992;Wahlsten et al, 2001).…”
Section: Abstract: Hippocampal Commissure; Memory; Learning; Ltp; Fementioning
confidence: 99%
“…Subjects were 24-month-old congenic mice (having primarily a C57BL/6J background; n = 16 females, n = 14 males), raised and group-housed in the Laboratory Animal Care Facility at The University at Albany [12,93].…”
Section: Subjects and Housingmentioning
confidence: 99%